The influence of perception on community behavior in managing household waste and toilet activities on the banks of the Martapura River, Banjar regency - Iqra, Muhammad; Wydiamala, Erida; Sanyoto, Didik Dwi; Herawati, Herawati; Istiqomah, Ermina (Institute of Computer Science (IOCS), 2025)
Martapura River, as one of the main rivers in South Kalimantan Province, plays a vital role in the lives of the people in Banjar Regency. However, many residents still dispose of household waste directly into the river and use floating latrines for bathing, washing, and defecating (MCK), a practice that continues to this day. Misperceptions can trigger behaviors that do not support river preservation and increase pollution. This study aims to analyze the influence of perceptions on community behavior in waste management and MCK activities. The research employs a quantitative approach with a cross-sectional design involving 100 respondents from communities along the Martapura River selected through purposive sampling. Data were statistically analyzed using the Structural Equation Modeling (SEM) with a 95% confidence level. Result showed that the community perceptions on waste management and MCK (bathing, washing and toilet) activities have a significant influence on their behavior (p-value <0.001).